Herlyn-Werner-Wünderlich syndrome: An unusual case with presentation of menorrhagia - Hsin-I Liang; Shao-Chi Fu; Chih-Hsiang Yin; Cheng-Chang Chang (Elsevier, 2020)
Objective: Herlyn-Werner-Wünderlich (HWW) syndrome is a rare condition in which patients present with a palpable pelvic mass and pain caused by an obstructed hemivagina. Here we present a case of HWW syndrome characterized by prolonged menstrual bleeding. Case report: A 19-year-old nonsexually active unmarried women experienced irregular menstrual cycles and menorrhagia. The duration of menstrual bleeding was 10-14 days. She also suffered from mild dysmenorrhea since menarche at the age of 13. Transabdominal sonography revealed a double uterus and a heterogeneous myoma-mimicking mass over the left cervical region. The left kidney was absent. Magnetic resonance imaging revealed a double uterus, a double vagina with an unperforated left hemivagina, and ipsilateral renal agenesis. The patient underwent cervicovaginal orifice reconstruction surgery. Conclusion: Left hematocolpos compression, a partially obstructed right vaginal channel, and an orifice with local venous drainage abnormalities resulted in prolonged menstrual bleeding. In HWW syndrome, the occurrence of a pelvic mass and pain is common; however, prolonged menstrual bleeding is rare.